Mxene materials based printed flexible devices for healthcare, biomedical and energy storage applications - Nicolosi, Valeria (My University, 2021)
The advent of cost effective printed smart devices has revolutionized the healthcare sector by allowing disease prediction and timely treatment through non-invasive real time and continuous health monitoring. Future advancements in printed electronic (PE) materials will continue to enhance the quality of human living. For any PE application, materials should possess proper mechanical integrity and resistivity while being non-toxic. In the case of sensing devices for physiological and biochemical signals, excellent conductivity is an essential requirement for obtaining high response signals. The emergence of the novel class of 2D materials called MXenes and their composites has resulted in structures and materials hugely relevant for healthcare devices. Exploiting solution based 2D MXene materials can expedite their practical application in PE devices by overcoming the present limitations of conductive inks such as poor conductivity and the high cost of alternative functional inks. There has been much progress in the MXene functional ink generation and its PE device applications since its discovery in 2011. This review summarizes the MXene ink formulation for additive patterning and the development of PE devices enabled by them in healthcare, biomedical and related power provision applications.
Keywords: MXene materials; printed smart devices; health monitoring